Tribulus terrestris in Management of Sexual Functions - Mahboubi, Mohaddese (Natural Products Journal, The, 2019)
Backgrounds: Tribulus terrestris (Zygophyllaceae family) is believed to have aphrodisiac activity in different cultures. Objective: The aim of this study was to evaluate the efficacy of T. terrestris in the management of sexual functions in female and male patients. Methods: We searched in PubMed Central, Science Direct, Wiley, Springer, SID, accessible books, reports, and thesis. Results: According to the results of animal and human studies, standard T. terrestris improved erectile parameters. After administration of T. terrestris, an increase in testosterone level was observed in most animal studies, while this increase was not confirmed in male human studies. T. terrestris improved the sperm parameters in animal and human studies. T. terrestris enhanced the folliculogenesis and improved polycystic ovary syndrome (PCO) in animal studies. The human clinical studies confirmed its efficacy on female sexual disorders. Conclusion: Therefore, standard T. terrestris extract as a valuable herbal compound can be considered an improvement of sexual functions in both sexes.
Keywords: sexual function